Online Booking Website Design with Design Thinking Method at Larissa Salon Studio, Binjai - Gunawan Manurung, Martin; Andhika Putri , Nadya; Indra Permana , Aminuddin (Cattleya Darmaya Fortuna, 2024)
This research investigates the development and implementation of an online booking system for Larissa Salon Studio in Binjai, utilizing the Design Thinking Method. The study addresses the challenges faced by the salon in managing appointments and promoting services through social media, which often led to inaccuracies and inefficiencies. By employing a structured approach that includes needs assessment, design, prototyping, testing, and evaluation, the research proposes a user-friendly website that facilitates seamless appointment scheduling and enhances customer engagement. The findings reveal that the newly developed system significantly improves operational efficiency while aligning with user needs. The website features two user account roles—user and admin—offering functionalities such as service viewing, booking, and rescheduling. The interface is designed to be intuitive and has been tested with real users at Larissa Salon Studio. Ultimately, this research contributes to the salon's business growth by providing a centralized platform for service management and customer interaction, thereby enhancing overall service delivery in the digital age.